1995
DOI: 10.1099/00221287-141-1-221
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of determinants encoding F1652 fimbriae from porcine septicaemic Escherichia coli confirms their identity as F1C fimbriae

Abstract: Foy, Quebec, Canada GlV4G5 ~ Cloning of the f165, operon that encodes F1C-like fimbriae in Escherichia coli indicates that this operon is a member of the S/Foc family. The genetic determinant coding for the F165, fimbriae was cloned from the chromosome of the porcine E. coli wild-type strain 4787 (01 15: K-l : H51: F165). The cloned F165, and the wild-type operon expressed a major fimbrial protein subunit of molecular mass 17.2 kDa that was detected by anti-F165 and anti-FlC polyclonal sera. The sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…F1C fimbriae are produced by E. coli causing UTI in humans[16]. In addition F165 2 fimbriae, which are homologous to F1C fimbriae, are expressed by F165‐positive E. coli associated with porcine septicemia and diarrhea [14, 23]. However, it is unknown whether these fimbriae contribute to the pathogenicity of E. coli implicated in either human UTI or porcine extraintestinal or intestinal disease.…”
Section: Resultsmentioning
confidence: 99%
“…F1C fimbriae are produced by E. coli causing UTI in humans[16]. In addition F165 2 fimbriae, which are homologous to F1C fimbriae, are expressed by F165‐positive E. coli associated with porcine septicemia and diarrhea [14, 23]. However, it is unknown whether these fimbriae contribute to the pathogenicity of E. coli implicated in either human UTI or porcine extraintestinal or intestinal disease.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of fimbrial extracts and Western blotting. Preparation of fimbrial extracts and Western blotting were performed as described previously (20), with anti-FimA serum from E. coli strain B AM and F1C fimbria-specific (anti-F165 2 ) antiserum (35).…”
Section: Methodsmentioning
confidence: 99%
“…The regulatory region of foo shares more than 96% identity with that of the pyelonephritis-associated pili (pap) gene. Previous work showed that F165 1 fimbriae are essential for virulence and survival during systemic stages of infection in young pigs (5)(6)(7)(8). F165 1 fimbriae are principally found in infections caused by opportunistic E. coli in animals, while Pap fimbriae are found in human clinical cases of urinary tract infections.…”
mentioning
confidence: 99%